Silane-stabilized nickel-doped nano zero-valent iron particle, preparation method and application

By introducing silane coupling agent during the preparation process, silane-stable nickel-doped nano zero-valent iron particles are prepared, which solves the problem of easy agglomeration and oxidation of iron-nickel bimetallic zero-valent iron, and achieves high efficiency for halogenated antibiotics degradation.

CN119387601AActive Publication Date: 2025-02-07ZHEJIANG UNIV

Patent Information

Application Number
CN202411446606.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-07
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The prior art is prone to agglomeration and oxidation when using iron-nickel bimetallic zero-valent iron, resulting in a decrease in specific surface area and reaction activity, low efficiency, long time consumption, and incomplete degradation.

Method used

By introducing silane coupling agent into the preparation process, silane-stable nickel-doped nano zero-valent iron particles are prepared by using mechanical ball milling and liquid phase reduction reaction to prevent the oxidation of zero-valent iron and protect their reaction sites.

Benefits of technology

The degradation efficiency of halogenated antibiotic pollutants has been significantly improved. Ni-doped nano zero-valent iron can efficiently degrade chloramphenicol and frefenicol in a short period of time, and the reaction rate constant is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119387601A_ABST
    Figure CN119387601A_ABST
Patent Text Reader

Abstract

The invention discloses a nickel-doped nano zero-valent iron particle with stable silane as well as a preparation method and application of the nickel-doped nano zero-valent iron particle. The nickel-doped nano zero-valent iron particles are mainly prepared by mixing silane, a mixed solution containing ferric salt and nickel salt and a reducing agent, and the specific preparation method comprises the following steps: adding the silane into the mixed solution containing ferric salt and nickel salt, carrying out anaerobic aeration, and carrying out ball milling and mixing in a planetary ball milling tank to obtain a precursor solution; and adding a reducing agent into the obtained precursor solution, continuously stirring after the reaction is completed, and carrying out vacuum freeze drying to obtain the nickel-doped nano zero-valent iron particles with stable silane. According to the method, the technical bottlenecks of low efficiency, long time consumption, incomplete degradation and the like of the existing iron-nickel bimetal type zero-valent iron in practical application are well solved, meanwhile, the problem that nano zero-valent iron is easy to passivate is solved, and the degradation efficiency of the obtained material on halogenated antibiotic pollutants is remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of antibiotic degradation, and in particular relates to silane-stabilized nickel-doped nano zero-valent iron particles, a preparation method and an application thereof. Background Art

[0002] Antibiotics are drugs for treating bacterial infections and are widely used in the animal husbandry industry. my country ranks first in the world in terms of the production and export volume of antibiotics. The harmful effects of the abuse of antibiotics on the environment are long-term and hidden. It is a new type of environmental pollution and has not received enough attention. Among them, halogenated antibiotics have stronger toxic effects due to the presence of halogen substituents, and are difficult to degrade naturally in the environment. They will pose a threat to organisms in the environment and damage the balance of the ecosystem. Zero-valent iron is a widely used reducing material. It has great advantages in the nitro reduction of chloramphenicol, but the dehalogenation effect is limited. The presence of halogen substituents will cause the degradation products of chloramphenicol to still have potential hazards. Iron-nickel bimetallic zero-valent iron can induce the galvanic cell effect, enhance the electron transfer efficiency of zero-valent iron, and thus have stronger reduction efficiency and show great dehalogenation advantages. However, iron-nickel bimetallic zero-valent iron also has the disadvantages of easy agglomeration and easy oxidation in practical applications, resulting in reduced specific surface area and reaction activity, showing low efficiency, long time consumption, and incomplete degradation. Therefore, it is very necessary to develop efficient, convenient, economical and stable bimetallic nano zero-valent iron.

[0003] Nano-zero-valent iron is an effective material for reducing and dehalogenating. However, the iron oxide passivation layer produced during the oxidation reaction of nano-zero-valent iron hinders electron transfer, which is an important factor limiting its further application in dehalogenation reactions. Adding secondary metals (such as Ni, Cu metals) can enhance the electronic reaction efficiency of zero-valent iron, but the strong reaction activity also makes it difficult to preserve and prone to passivation. Therefore, obtaining a stable bimetallic nano-zero-valent iron material is the key to using iron-based reducing materials to detoxify halogenated antibiotics. Summary of the invention

[0004] In order to solve the problems and defects in the background technology, the purpose of the present invention is to provide a method for degrading chloramphenicol in water by using silane-stabilized nickel-doped nano zero-valent iron. The provided silane coupling agent is commonly used for metal corrosion protection. The silane coupling agent is introduced. During the hydrolysis and condensation of silane, the organic silane is grafted onto the surface of the zero-valent iron metal to prevent it from being further oxidized, thereby protecting the reaction sites of the zero-valent iron. The material preparation method is simple, and the obtained material significantly improves the degradation efficiency of halogenated antibiotic pollutants.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] 1. A silane-stabilized nickel-doped zero-valent iron nanoparticle, characterized in that:

[0007] The nickel-doped nano zero-valent iron particles are mainly prepared by mixing a mixed solution containing iron salt and nickel salt, silane and a reducing agent. In the present invention, organic silane, iron salt and nickel salt are mixed by mechanical ball milling, and then liquid phase reduction reaction is carried out, and silane-stabilized nickel-doped nano zero-valent iron is obtained after vacuum freeze drying.

[0008] 2. A method for preparing silane-stabilized nickel-doped nano zero-valent iron particles, the steps of the method are as follows:

[0009] (1) adding silane to a mixed solution containing iron salt and nickel salt, performing anaerobic aeration, and then ball milling and mixing in a planetary ball mill to obtain a precursor solution;

[0010] (2) Adding a reducing agent to the obtained precursor solution, and after the reaction is complete, continuing stirring, and vacuum freeze-drying to obtain silane-stabilized nickel-doped zero-valent iron nanoparticles.

[0011] The silane in step (1) is any one of trimethoxysilane and 3-aminopropylmethoxysilane, the iron salt is ferric chloride hexahydrate, the nickel salt is nickel chloride hexahydrate, the reducing agent in step (2) is sodium borohydride, and the planetary ball mill is a zirconia ball mill.

[0012] The solvents of the mixed solution in step (1) are ethanol and deionized water, and the volume ratio of ethanol to deionized water is 1:1.

[0013] In the step (1), the molar ratio of silane, nickel salt and iron salt is 0.5-5:0.5-1.5:100.

[0014] In the step (1), silane is added dropwise to the mixed solution of iron salt and nickel salt, nitrogen is passed through for 30 minutes for anaerobic aeration, and the ball milling speed is 600 revolutions per minute for 24 hours.

[0015] In the step (2), the stirring time is 2 hours and the vacuum freeze-drying time is 36 hours.

[0016] 3. Use nickel-doped nano zero-valent iron particles in the degradation of antibiotics.

[0017] 4. A method for degrading antibiotics using nickel-doped nano zero-valent iron particles, wherein the method comprises adjusting the pH of the antibiotic solution to be degraded before degradation, adding the obtained silane-stabilized nickel-doped nano zero-valent iron particles to the antibiotic solution to be degraded or the antibiotic pollutants after the pH is adjusted, and then performing closed oscillation to achieve degradation.

[0018] Preferably, the antibiotic is a halogenated antibiotic.

[0019] The silane-stabilized nickel-doped nano zero-valent iron particles are added to an antibiotic solution to be degraded at a dosage of 1 g / L. The antibiotics are chloramphenicol and florfenicol. The concentration of chloramphenicol is 20 mg / L, and the concentration of florfenicol is 20 mg / L.

[0020] The concentration of the antibiotic in the reaction system is determined by adding the obtained silane-stabilized nickel-doped zero-valent iron nanoparticles into a solution of the antibiotic and sealing and shaking the reaction.

[0021] The dosage of the silane-stabilized nickel-doped zero-valent iron material is 1 g / L, the antibiotics are chloramphenicol and florfenicol, the concentration of chloramphenicol is 20 mg / L, and the concentration of florfenicol is 20 mg / L.

[0022] The pH was adjusted to 7.0. The concentration of antibiotics was determined by sacrificial sampling method, using a syringe to take 2 ml of the reaction solution from a sealed container, filtering it and then detecting the antibiotic concentration by high performance liquid chromatography.

[0023] Compared with the prior art, the advantages of the present invention are:

[0024] 1. The present invention provides a method for preparing a silane-stabilized nickel-doped nano zero-valent iron material. The particle size of the silane-stabilized nickel-doped nano zero-valent iron is about 50 to 80 nm, and the iron content is higher than 70%wt.

[0025] 2. The degradation efficiency of florfenicol by 3-methoxysilane-stabilized nickel-doped nano-zero-valent iron is as high as 95% within 30 minutes, which is better than that of unmodified zero-valent iron, and the reaction rate constant is about 60 times that of unmodified zero-valent iron.

[0026] 3. The degradation efficiency of chloramphenicol by 3-aminopropylmethoxysilane-stabilized nickel-doped nano-zero-valent iron is as high as 95% within 5 minutes under the scheme provided by the present invention, and the reaction rate constant is about 20 times that of unmodified zero-valent iron.

[0027] In summary, the nickel-doped nano zero-valent iron obtained by the preparation method of silane-stabilized nickel-doped nano zero-valent iron provided by the present invention improves the electron transfer efficiency and anti-interference ability of the material, can quickly degrade halogenated antibiotics, completely dechlorinate chloramphenicol and completely defluorinate florfenicol, has a simple modification method, and has extremely high application value in water treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 TEM image of the preparation of silane-stabilized nickel-doped nano-zero-valent iron;

[0029] Figure 2 Element content diagram for preparing silane-stabilized nickel-doped nano zero-valent iron;

[0030] Figure 3 This is a comparison chart of the effect of preparing silane-stabilized nickel-doped nano zero-valent iron on degrading florfenicol;

[0031] Figure 4 A comparison chart of the effect of preparing silane-stabilized nickel-doped nano-zero-valent iron on the degradation of chloramphenicol;

[0032] Figure 5 The effect diagram of different proportions of 3-methoxysilane and different proportions of nickel-doped nano zero-valent iron on the degradation of florfenicol;

[0033] Figure 6 The effect diagram of different proportions of 3-aminopropylmethoxysilane and different proportions of nickel-doped nano zero-valent iron on the degradation of florfenicol;

[0034] Figure 7 This is a comparison chart of the effect of preparing silane-stabilized nickel-doped nano-zero-valent iron to degrade chloramphenicol under the influence of nitrate. Figure 7 a is the degradation effect of 3-methoxysilane-stabilized nickel-doped nano-zero-valent iron. Figure 7 b is the degradation effect of nickel-doped nano-zero-valent iron stabilized by 3-aminopropylmethoxysilane;

[0035] Figure 8 This is a diagram showing the degradation of chloramphenicol by 3-aminopropylmethoxysilane-stabilized nickel-doped nano-zero-valent iron under the combined influence of oxygen and nitrate;

[0036] Fig. 9 This is the TEM morphology of silane-stabilized nickel-doped nano-zero-valent iron in Example 1. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and specific operation process are given, but the protection authority of the present invention is not limited to the following embodiments.

[0038] In the following comparative tests and examples, unless otherwise specified, the raw materials and instruments used are commercially available, the processes used are conventional processes, the equipment used are conventional equipment, and the data obtained are the average values ​​of more than three repeated experiments.

[0039] Embodiments of the present invention are as follows:

[0040] Fig. 9 It is not necessary to describe it. The one used for the summary diagram is ZVI-Ni-NH in Example 1. 2 Si

[0041] Example 1

[0042] The silane-stabilized nickel-doped nano-zero-valent iron material was prepared by mixing by mechanical ball milling and combining with a liquid phase reduction method. The preparation steps are as follows:

[0043] (1) Zirconia beads of different particle sizes (particle sizes of 1 mm, 2 mm, 4 mm, and 6 mm, with a number of 10 beads) were placed in a zirconia ball mill as sand mill media;

[0044] (2) 20 ml of a mixed solution of silane, nickel salt, and iron salt (molar ratio of 1:1:100) was placed in a ball mill and nitrogen was passed through the mill for 30 min;

[0045] (3) Turn on the ball mill, adjust the ball mill speed to 600 rpm, and ball mill for 24 hours to obtain a precursor solution;

[0046] (4) Under the protection of nitrogen, reduce the iron-nickel precursor with sodium borohydride and stir for 2 hours;

[0047] (5) The obtained silane-stabilized nickel-doped nano-zero-valent iron particles were washed with water and then dried in a freeze drying oven for 36 hours to obtain silane-stabilized nickel-doped nano-zero-valent iron.

[0048] The results show that Figure 1 and Figure 2 The particle size of the silane-stabilized nano-zero-valent iron is 50 to 80 nanometers, showing typical nano-zero-valent iron crystal characteristics, and the iron content is higher than 70%wt.

[0049] At the same time, the TEM morphology of the silane-stabilized nickel-doped nano-zero-valent iron in Example 1 at a scale of 50 nm is as follows Fig. 9 shown.

[0050] In this embodiment, silanes used were trimethoxysilane and 3-aminopropylmethoxysilane to prepare silane-stabilized nickel-doped nano zero-valent iron ZVI-Ni-CH 3 Si, ZVI-Ni-NH 2 Si, wherein the molar ratio of silane, nickel salt and iron salt is 1:1:100.

[0051] Comparison test 1

[0052] The specific steps are:

[0053] Accurately weigh 50 mg of silane-stabilized nickel-doped nano-zero-valent iron (ZVI-Ni-CH containing 1% Ni molar amount and 1% Si molar amount) prepared in Example 1. 3 Si, ZVI-Ni-NH containing 1% Ni by mole and 1% Si by mole 2Si) and unmodified nano zero-valent iron (ZVI) were added to 50 mL of 20 mg / L florfenicol solution after nitrogen aeration and adjusted to pH 7, and the solution was strictly sealed. The solution was shaken in a shaker for 2 hours, and 2 mL of the solution was extracted from the sealed bottle with a syringe at regular intervals, and the concentration of florfenicol was detected by high performance liquid chromatography after filtration.

[0054] The results show that if Figure 3 As shown in the figure, under anaerobic conditions, the degradation time of ZVI-Ni-CH containing 1% Ni and 1% Si was 30 minutes. 3 Si, ZVI-Ni-NH containing 1% Ni by mole and 1% Si by mole 2 The removal efficiency of Si and unmodified nano-zero-valent iron ZVI on florfenicol was 94.9%, 76.3% and 8%, respectively. The degradation rate constant was 0.12min -1 , 0.055min -1 , 0.002min -1 .

[0055] Comparison Test 2

[0056] Same as comparative test 1, except that the antibiotic solution is 20 mg / L chloramphenicol.

[0057] The results show that if Figure 4 As shown in the figure, within 5 minutes of degradation, ZVI-Ni-CH 3 Si, ZVI-Ni-NH containing 1% Ni by mole and 1% Si by mole 2 The removal efficiency of Si and ZVI for chloramphenicol was 68.3%, 95.5% and 12.3% respectively. The degradation rate constant was 0.42min -1 , 0.129min -1 , 0.021min -1 .

[0058] Example 2

[0059] Accurately weigh 50 mg of silane-stabilized nickel-doped nano-zero-valent iron and mix the ZVI-Ni-CH 3 Si, ZVI-Ni-CH containing 1% Ni and 1% Si 3 Si, ZVI-Ni-CH containing 1% Ni and 2% Si 3 Si, ZVI-Ni-CH containing 1% Ni and 5% Si 3Si, ZVI-Ni-CH containing 0.5% Ni by mole and 1% Si by mole 3 Si, ZVI-Ni-CH containing 1.5% Ni and 1% Si 3 Si was added to 50 mL of 20 mg / L florfenicol solution adjusted to pH 7 and aerated with nitrogen, and the solution was tightly sealed. The solution was shaken in a shaker for 2 h. At regular intervals, 2 mL of the solution was extracted from the sealed bottle with a syringe, filtered, and tested with a high performance liquid chromatograph. The results showed that Figure 5 It is shown that maintaining the proportion of methylsilane at 1-2% and maintaining the proportion of nickel at 1% has the best degradation effect on florfenicol.

[0060] Example 3

[0061] Same as Example 2, except that the silane-stabilized nickel-doped nano-zero-valent iron is ZVI-Ni-NH 2 Si, ZVI-Ni-NH containing 1% Ni by mole and 1% Si by mole 2 Si, ZVI-Ni-NH containing 1% Ni and 2% Si 2 Si, ZVI-Ni-NH containing 1% Ni and 5% Si 2 Si, ZVI-Ni-NH containing 0.5% Ni and 1% Si 2 Si, ZVI-Ni-NH containing 1.5% Ni and 1% Si 2 Four.

[0062] The results showed that Figure 6 It is shown that maintaining the ratio of aminosilane at 1-2% and maintaining the ratio of nickel at 1% has the best degradation effect on florfenicol.

[0063] Example 4

[0064] Accurately weigh 50 mg of silane-stabilized nickel-doped nano-zero-valent iron containing 1% Ni molar amount and 1% Si molar amount of ZVI-Ni-CH 3 Si, ZVI-Ni-NH containing 1% Ni by mole and 1% Si by mole 2 Si was added to 50 mL of 20 mg / L chloramphenicol solution after nitrogen aeration and pH adjustment to 7, and the concentration of coexisting nitrate in the solution was 0, 5, 10, and 20 mg / L, respectively. The solution was tightly sealed. Oscillating in a shaker for 2 hours, 2 mL of solution was extracted from the sealed bottle with a syringe at regular intervals, and the concentration of chloramphenicol was detected by high performance liquid chromatography after filtering.

[0065] The results show that if Figure 7 As shown, when the nitrate concentration is 0-20 mg / L, the nickel-doped nano zero-valent iron material stabilized by 3-aminopropylmethoxysilane can complete the degradation of chloramphenicol in 20 minutes, with high electron transfer efficiency and strong anti-interference ability.

[0066] Comparison test 3

[0067] The same as Example 3, except that the chloramphenicol degradation solution in which nitrate coexists does not undergo a nitrogen aeration process, that is, it is maintained as an aerobic solution.

[0068] The results show that if Figure 8 As shown, under aerobic conditions, the nitrate concentration is 0-20 mg / L, and the chlorine degradation of chloramphenicol by the nickel-doped nano-zero-valent iron material stabilized by 3-aminopropylmethoxysilane is maintained at more than 80% in 5 minutes, has strong resistance to competitive reactions, and has a stable degradation effect.

[0069] The above description is only a specific implementation of the present invention, but the protection scope of the present invention is not limited thereto. Any person familiar with the technology can understand and think of any changes or substitutions within the technical scope disclosed by the present invention, which should be included in the scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A silane-stabilized nickel-doped zero-valent iron nanoparticle, characterized in that: The nickel-doped nano zero-valent iron particles are mainly prepared by mixing a mixed solution containing iron salt and nickel salt, silane and a reducing agent.

2. A method for preparing silane-stabilized nickel-doped zero-valent iron nanoparticles, characterized in that: The steps of the method are as follows: (1) adding silane to a mixed solution containing iron salt and nickel salt, performing anaerobic aeration, and then ball milling and mixing in a planetary ball mill to obtain a precursor solution; (2) Adding a reducing agent to the obtained precursor solution, and after the reaction is complete, continuing stirring, and vacuum freeze-drying to obtain silane-stabilized nickel-doped zero-valent iron nanoparticles.

3. The method for preparing silane-stabilized nickel-doped zero-valent iron nanoparticles according to claim 1, characterized in that: The silane in step (1) is any one of trimethoxysilane and 3-aminopropylmethoxysilane, the iron salt is ferric chloride hexahydrate, the nickel salt is nickel chloride hexahydrate, the reducing agent in step (2) is sodium borohydride, and the planetary ball mill is a zirconia ball mill.

4. The method for preparing silane-stabilized nickel-doped zero-valent iron nanoparticles according to claim 1, characterized in that: The solvents of the mixed solution in step (1) are ethanol and deionized water, and the volume ratio of ethanol to deionized water is 1:

1.

5. The method for preparing silane-stabilized nickel-doped zero-valent iron nanoparticles according to claim 1, characterized in that: In the step (1), the molar ratio of silane, nickel salt and iron salt is 0.5-5:0.5-1.5:

100.

6. The method for preparing silane-stabilized nickel-doped zero-valent iron nanoparticles according to claim 1, characterized in that: In the step (1), silane is added dropwise to the mixed solution of iron salt and nickel salt, nitrogen is passed through for 30 minutes for anaerobic aeration, and the ball milling speed is 600 revolutions per minute for 24 hours.

7. The method for preparing silane-stabilized nickel-doped zero-valent iron nanoparticles according to claim 1, characterized in that: In the step (2), the stirring time is 2 hours and the vacuum freeze-drying time is 36 hours.

8. Use of the silane-stabilized nickel-doped zero-valent iron nanoparticles according to claim 1 or the silane-stabilized nickel-doped zero-valent iron nanoparticles prepared by the preparation method according to any one of claims 2 to 7 in the degradation of antibiotics.

9. A method for degrading antibiotics using the silane-stabilized nickel-doped nano zero-valent iron particles according to claim 1 or the silane-stabilized nickel-doped nano zero-valent iron particles prepared by the preparation method according to any one of claims 2 to 7, characterized in that: The method comprises the following steps: adjusting the pH of an antibiotic solution to be degraded before degradation; adding the obtained silane-stabilized nickel-doped nano zero-valent iron particles to the antibiotic solution to be degraded or antibiotic pollutants after the pH is adjusted; and then performing closed oscillation to achieve degradation.

10. A method for degrading antibiotics using silane-stabilized nickel-doped nano zero-valent iron particles according to claim 9, characterized in that: The silane-stabilized nickel-doped nano zero-valent iron particles are added to an antibiotic solution to be degraded at a dosage of 1 g / L. The antibiotics are chloramphenicol and florfenicol. The concentration of chloramphenicol is 20 mg / L, and the concentration of florfenicol is 20 mg / L.

Citation Information

Patent Citations

  • Nano zero-valent iron-nickel composite material prepared on basis of laterite-nickel ore and preparation method of nano zero-valent iron-nickel composite material

    CN110732679A

  • Method for efficiently removing heavy metals in water body based on lignosulfonate modified cobalt-doped zero-valent iron composite material

    CN115432796A

  • Silicified modified zero-valent iron and its preparation method and application

    US20220118516A1

  • Nanoparticles of co complexes of zero-valent metals that can be used as hydrosilylation and dehydrogenative silylation catalysts

    WO2019138194A1

Cited By

  • Zero-valent iron protection catalytic membrane as well as preparation method and application thereof

    CN120618528A